Kesadaran Hukum dan Partisipasi Politik Pada Pemilu 2019 - Derby Kanti Nirvana; Trianah Sofiani (Department of Constitutional Law, Faculty of Sharia, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study analyzes the legal awareness of the communi5ty in the general election and its implications for political participation, especially among the people in Pemalang Regency. They were referring to the Pemalang district general election in 2019 and that the community should actively participate in the general election process. However, based on the results of interviews with the community, it shows that the community’s understanding or mindset in the implementation of the general election, is often faced with deeprooted obstacles, ranging from the low level of understanding and ability of the community to implement democracy, as well as confusion about how to participate through legal, constitutional and moral political procedures and methods. This study aimed to determine the legal awareness of the people of Pemalang Regency in the 2019 general election and the implications of public legal awareness on political participation. This study uses a type of empirical juridical research, namely where the research is carried out by combining legal materials with data obtained from the field. With the type of qualitative research approach. Based on the results of the study, it can be concluded that the public’s understanding of the contents of the regulations is still relatively shallow because they do not know how the goals and missions of the regulations that have been made and new policies in the general election strategy.